Bioactive properties, antibacterial activity, and color features of Polygonum cognatum: The effects of frozen storage and cooking process - Demirgul, Furkan; Divriklioglu-Kundak, Melike; Sagdic, Osman (SOC BRASILEIRA CIENCIA TECNOLOGIA ALIMENTOS, 2022)
In this study, the effects of frozen storage (for six months at -30 ??C) and cooking on total phenolic, antioxidant activity and color characteristics of Polygonum cognatum Meissn. were determined. In addition, the antibacterial activity of the ethanol extract of the plant against Escherichia coli, Salmonella Typhimurium, Staphylococcus aureus, Bacillus subtilis, and B. cereus was investigated. Both frozen storage and cooking have been found to cause significant decreases in the total phenolics. During the storage, differences among DPPH radical scavenging activities were statistically insignificant. However, the DPPH activity has been found to increase significantly with cooking. Copper-reducing antioxidant capacity has started to decrease considerably after four months of storage. Cooking process slightly increased the copper-reducing capacity. Various changes were detected in the color properties of both frozen stored and cooked samples. The ethanol extract of the plant was effective against all the tested bacteria at different ratios.
Keywords: Polygonum cognatum Meissn; madimak; frozen storage; cooking; bioactivity; color characteristics; RADICAL-SCAVENGING ACTIVITY; TOTAL ANTIOXIDANT CAPACITY; VITAMIN-C; THERMAL-TREATMENT; TOTAL PHENOLICS; IN-VITRO; EXTRACTS; VEGETABLES; PLANT; ACID; Food Science & Technology